A novel vaccine platform using glucan particles for induction of protective responses against Francisella tularensis and other pathogens. (12th September 2019) - Abraham, A; Ostroff, G; Levitz, S M; Oyston, P C F
Summary: Vaccines are considered the bedrock of preventive medicine. However, for many pathogens, it has been challenging to develop vaccines that stimulate protective, long-lasting immunity. We have developed a novel approach using β-1, 3-D-glucans (BGs), natural polysaccharides abundantly present in fungal cell walls, as a biomaterial platform for vaccine delivery. BGs simultaneously provide for receptor-targeted antigen delivery to specialized antigen-presenting cells together with adjuvant properties to stimulate antigen-specific and trained non-specific immune responses. This review focuses on various approaches of using BG particles (GPs) to develop bacterial and fungal vaccine candidates. A special case history for the development of an effective GP tularaemia vaccine candidate is highlighted. Graphical Abstract: